miRNA-mediated risk for schizophrenia in 22q11.2 deletion syndrome - Brzustowicz, Linda M.; Bassett, Anne S. (Frontiers in Genetics, 2012)
In humans, the most common genomic disorder is a hemizygous deletion of a 1.5 to 3 Mb region of chromosome 22q11.2. The resultant 22q11.2 deletion syndrome (22q11.2DS) can affect multiple organ systems, and most notably includes cardiac, craniofacial, and neurodevelopmental defects. Individuals with 22q11.2DS have a 20 to 25-fold risk of developing schizophrenia compared to individuals from the general population, making 22q11.2DS the strongest known molecular genetic risk factor for schizophrenia. Although the deleted region includes DGCR8, a gene coding for a miRNA processing protein, the exact mechanism by which this deletion increases risk is unknown. Importantly, several lines of evidence suggest that miRNAs may modulate risk for schizophrenia in other, non-22q11.2DS populations. Here we present a theory which mechanistically explains the link between 22q11.2DS, miRNAs, and schizophrenia risk. We outline the testable predictions generated by this theory and present preliminary data in support of our model. Further experimental validation of this model could provide important insights into the etiology of both 22q11.2DS and more common forms of schizophrenia.